Quality, functional and sensory evaluation of pasta fortified with extracts from Opuntia ficus‐indica cladodes. (19th March 2019) - Attanzio, Alessandro; Diana, Patrizia; Barraja, Paola; Carbone, Anna; Spanò, Virginia; Parrino, Barbara; Cascioferro, Stella M; Allegra, Mario; Cirrincione, Girolamo; Tesoriere, Luisa; Montalbano, Alessandra
Abstract: BACKGROUND: The stems of Opuntia ficus‐indica, known as cladodes, are a rich source of soluble fibers, which makes them an important candidate for the production of functional foods. Tagliatelle of durum wheat fortified with Opuntia cladode extract (OCE) at different levels of addition (10–30%, v/w) was prepared on a laboratory scale and quality characteristics and sensory acceptability were assessed. RESULTS: The main quality parameters (optimal cooking time, swelling index, cooking loss, dry matter) and sensory analysis on a nine‐point hedonic scale were comparable with those of the control pasta sample (no added OCE) when durum wheat was supplemented with OCE at up to 20% (v/w). An in vitro human simulated gastrointestinal digestion in the presence of cholesterol or its main dietary oxidized derivative, 7‐ketocholesterol, showed that OCE‐fortified pasta strongly reduced the bioaccessibility of both the sterols (the higher the incorporated OCE level, the higher the effect). Moreover the extent of starch digestion decreased with increasing levels of OCE. CONCLUSION: The results of the present study indicate that OCE‐fortified pasta comprises a food with healthy properties, such as blood cholesterol‐ and glucose‐lowering capabilities. © 2019 Society of Chemical Industry